The Effect Of Provision Of Physical Movement Activities On Increasing Basal Metebolism Rate In Diabetes Mellitus Patients In Namohalu Esiwa Puskesmas, Nias Utara Regency 2020 - Jenni Susi Sihite; Lely Desi Uli Basana; Wisna (Science Midwifery, 2020)
Diabetes mellitus (DM) is the most commonly determined endocrine disease. This disease is a metabolic disorder that is genetically and clinically heterogeneous with manifestations in the form of loss of carbohydrate tolerance, this heterogeneous disorder is characterized by increased levels of glucose (blood sugar) in the blood or hyperglycemia. Decreased physical activity causes a decrease in muscle mass and an increase in fat mass so that it This will have an impact on the body's own basal metabolism. The purpose of this study was to determine the effect of giving physical activity activity to increasing basal metabolism rate in patients with diabetes mellitus at the NamohaluEsiwa Public Health Center, NiasUrata Regency. This type of research used a quasi-experimental design. ), the sample was taken using the total population technique, namely all populations, namely all populations were used as a sample of 10 people. It was carried out from 03-31 July 2017. The research instrument was in the form of SOP for movement activities. Data analysis was used with an independent t test. The results of the study showed that there was an effect of giving movement activity to the basal metabolic rate value in NIDDM patients at the NamohaluEsiwa Public Health Center, North Nias Regency. The average BMR is 8.77%, on the effect of giving movement activity to the basal metabolic rate value in NIDDM. Therefore, improving service facilities for NIDDM sufferers, especially in physiotherapy problems on movement activity.